Performance of some early-maturing groundnut (Arachis hypogaea L.) genotypes and selection of high-yielding genotypes in the potato-fallow system - Gangadhara K; Ajay BC; Praveen Kona; Kirti Rani; Narendra Kumar; S. K. Bera (PLoS ONE, 2023)
India imports the most edible oils because domestic demand exceeds production. Horizontally expanding groundnut production in non-traditional areas especially in the potato-paddy rice-fallow system is possible for increasing production and it requires trait-specific cultivars. Only 1% of oilseeds are grown in non-traditional regions. Nine interspecific groundnut derivatives were tested in potato-fallow system at Deesa, Gujarat, and Mohanpura, West Bengal, and non-potato fallow areas in Junagadh during Kharif 2020 to examine their performance and adaptability. Genotype-by-environment (G×E) interaction significantly affected pod yield and its components in the combined ANOVA. "Mean vs. stability" showed that the interspecific derivative NRCGCS 446 and variety TAG 24 were the most stable and valuable genotypes. GG 7 yielded more pods in Junagadh, whereas NRCGCS 254 yielded more in Mohanpur. Low heritability estimates and strong G×E interaction for flowering days showed complicated inheritance and environmental effects. The shelling percentage was significantly correlated with days to 50% blooming, days to maturity, SCMR, HPW, and KLWR, demonstrating negative connections between maturity, component characteristics, and seed size realisation.